The yeast three-hybrid system as an experimental platform to identify proteins interacting with small signaling molecules in plant cells: Potential and limitations - Cottier, Stéphanie; Mönig, Timon; Wang, Zheming; Svoboda, Jiří; Boland, Wilhelm; Kaiser, Markus; Kombrink, Erich (Frontiers in Plant Science, 2011)
Chemical genetics is a powerful scientific strategy that utilizes small bioactive molecules as experimental tools to unravel biological processes. Bioactive compounds occurring in nature represent an enormous diversity of structures that can be used to dissect functions of biological systems. Once the bioactivity of a natural or synthetic compound has been critically evaluated the challenge remains to identify its molecular target and mode of action, which usually is a time consuming and labor-intensive process. To facilitate this task, we decided to implement the yeast three-hybrid (Y3H) technology as a general experimental platform to scan the whole Arabidopsis proteome for targets of small signaling molecules. The Y3H technology is based on the yeast two-hybrid system and allows direct cloning of proteins that interact in vivo with a synthetic hybrid ligand, which comprises the biologically active molecule of interest covalently linked to methotrexate (Mtx). In yeast nucleus the hybrid ligand connects two fusion proteins: the Mtx part binding to dihydrofolate reductase fused to a DNA binding domain (encoded in the yeast strain), and the bioactive molecule part binding to its potential protein target fused to a DNA activating domain (encoded on a cDNA expression vector). During cDNA library screening, the formation of this ternary, transcriptional activator complex leads to reporter gene activation in yeast cells, and thereby allows selection of the putative targets of small bioactive molecules of interest. Here we present the strategy and experimental details for construction and application of a Y3H platform, including chemical synthesis of different hybrid ligands, construction of suitable cDNA libraries, the choice of yeast strains, and appropriate screening conditions. Based on the results obtained and the current literature we discussed the perspectives and limitations of the Y3H approach for identifying targets of small bioactive molecules.